2013
DOI: 10.1177/000313481307900331
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Transfers and Definitive Imaging: Patient Benefit but at What Cost?

Abstract: Many patients undergo computed tomography (CT) scan before transfer to definitive care. Despite this, studies are often repeated on arrival to the trauma center. We evaluated a policy to provide formal in-house interpretation of images performed at outside hospitals. A 3-month retrospective analysis was performed. Two groups were compared. Patients in the in-house interpretation (IHI) group underwent in-house interpretation of outside images. Those images not meeting criteria were placed in the comparison grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Significant direct and indirect costs are associated with interfacility transfer and have important resource utilization implications. Patients who are transferred frequently undergo repeat imaging, resulting in increased radiation exposure, image billing, and total hospital costs [33,34]. Additionally, secondary overtriage has been identified as a potential area of cost escalation [35,36].…”
Section: Crudementioning
confidence: 99%
“…Significant direct and indirect costs are associated with interfacility transfer and have important resource utilization implications. Patients who are transferred frequently undergo repeat imaging, resulting in increased radiation exposure, image billing, and total hospital costs [33,34]. Additionally, secondary overtriage has been identified as a potential area of cost escalation [35,36].…”
Section: Crudementioning
confidence: 99%
“…The quality of the imaging has been described directly (e.g. imaging produced by one- to four-slice scanners providing less resolution, and technologist-dependent errors like contrast timing) and indirectly (via concern for missed injury despite the ability to view OSH imaging) [ 5 , 10 , 11 , 15 , 16 , 30 , 31 , 36 , 41 , 42 ]. One study found that injuries not described by referring hospital scans which were found upon rCT of the same region upon arrival at TCs accounted for 54% of repeat imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In a study dedicated to the matter, an American College of Surgeons Level I trauma center had in-house radiologists read outside images by way of the electronic medical record (EMR)-ordered consult. They addressed legal concerns by having NTC radiology reports uploaded to complete the consult [ 16 ]. The result was a statistically significant decrease in total CTs, including rCTs and those in every body region except the chest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations